Methods for testing short- and long-term phosphorus fertilizing efficiency of products with varying solubility - Kiani, Mina; Ylivainio, Kari (Elsevier, 2024)
Phosphorus (P) recovery from nutrient-rich side streams (NRSS) and derived products is crucial to ensure sustainable food production in the future and to enhance the circular economy, but the agronomic efficiency of these products needs to be validated to reach these targets. In this study, we used a Hedley fractionation scheme and the diffusive gradient in thin film (DGT) method to determine P availability in 83 NRSS and derived products originating from Finland, Sweden, and Germany. Furthermore, two independent short- and long-term growth experiments with barley (Hordeum vulgare L.) and ryegrass (Lolium perenne L.), respectively, were conducted to evaluate P availability in 15 selected NRSS. In addition to the DGT soil test, different fertilizer extractants, 2 % formic acid (FA), 2 % citric acid, and neutral ammonium citrate, were tested for predicting P availability in growth experiments. Livestock manures and slurries were found to contain a notable portion of labile P and were comparable to superphosphate (SP). Despite the low shares of labile P in struvite (7.2 %) and AshDec® (1.3 %), they exhibited P availability comparable to SP fertilizer, as indicated by DGT (99 % and 238 % of SP equivalence, respectively). This suggests that factors other than solubility influenced P availability in these side streams. The DGT method as a promising soil test predicted both short- and long-term P availability better than the selected conventional chemical extraction methods did. The 2 % FA extract exhibited the poorest performance, overestimating P availability in some nutrient sources while underestimating others in long-term. These findings enhance our understanding of P availability in potential raw materials for fertilizers, facilitating more effective P management strategies in the circular economy.
Keywords: DGT method; P availability; Recycled fertilizers; Relative agronomic efficiency; Sustainable P fertilizer production